2018
DOI: 10.30733/std.2018.01062
|View full text |Cite
|
Sign up to set email alerts
|

Can Neutrophil/Lymphocyte Ratio be Used As a Marker in The Diagnosis of Bullous Pemphigoid

Abstract: Amaç: Büllöz pemfigoid (BP) dermo-epidermal bileşkede yer alan antijenlere karşı oluşan antikorların neden olduğu, sıklıkla ileri yaş döneminde izlenen büllöz bir dermatozdur. Otoantikorların tetiklediği inflamasyon sonucunda hasta serumlarında ve büllerde inflamatuar mediatörlerin artmış olduğu ve artan bu mediatörlerin hastalık şiddeti ile ilişkili olabileceği bildirilmiştir. Nötrofil lenfosit oranı (NLO); nötrofil sayısının lenfosit sayısına bölünmesi ile elde edilen; daha önce ürtiker, psoriazis, pemfigus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
7
1
1
Order By: Relevance
“…9 In the study of Ozer et al,there was no difference in MPV value between the patients with BP and the control group. 10 In our study, MPV levels were higher in the control group, but there was no significant difference between the two groups. This result suggests that MPV may not be a reliable indicator of inflammation in BP.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…9 In the study of Ozer et al,there was no difference in MPV value between the patients with BP and the control group. 10 In our study, MPV levels were higher in the control group, but there was no significant difference between the two groups. This result suggests that MPV may not be a reliable indicator of inflammation in BP.…”
Section: Discussioncontrasting
confidence: 53%
“…23 In the study of Ozer et al, patients with bullous pemphigoid, neutrophil count and NLR were found to be significantly higher in BP patients when compared to the controls. 10 In our study, NLR was found to be higher in BP patients when compared to the age and gender matched control patients. The result in our study may lead to the consideration that NLR might be a practical and cheap indicator of inflammation in BP.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Sistemik İnflamasyonun belirteçlerinden olan NLO parametresi son dönem yapılan çalışmalarda, özellikle patogenezinde inflamatuar süreçlerin etkili olduğu hastalıklarda, önemli bir parametre olarak gösterilmektedir. Birçok kronik hastalığın alevlenmesinde takip kriteri olarak kullanılabileceğine dair çalışmalar mevcuttur (9). Bizim çalışmamızda da hipertansiyon hastalığının kronik bir süreç olması ve patogenezinde damarlarda gelişen inflamatuar süreçlerin sistemik etkilerinin olması sebebiyle bu belirteç kullanılmıştır.…”
Section: Discussionunclassified
“…There is an ample number of studies in current literature which show that NLR points to bad prognosis. NLR is an easily-obtained value in determining systemic inflammation and prognosis (6)(7)(8)15,16). Increases in WBC may not be seen in elderly patients because of age-related anergia but increases in NLR, which is an indicator of systemic inflammation, are seen.…”
Section: Discussionmentioning
confidence: 99%